The Role of Social Capital Theory in the Development of Effective Religious Volunteerism - Wicks, Don A.; Freeburg, Darin (Proceedings of the Annual Conference of CAIS / Actes du congrès annuel de l’ACSI, 2013)
This study considers the impact of church involvement on social capital (SC) levels, and the impact of these levels on church volunteerism. SC theory suggests that relationships are established with a purpose in mind and that the aim of the individual is to use these relationships in a beneficial way. This theory drives the research hypotheses and findings of the study. It is hypothesized that church involvement has a positive correlation with higher levels of SC, and that SC has a positive correlation with volunteerism. SC, therefore, is seen as a mediating variable linking increased church involvement with increased volunteerism. Cette étude prend en considération l’impact de l’implication religieuse sur les niveaux de capital social et l’impact de ces niveaux sur le bénévolat religieux. La théorie du capital social suggère que les relations s’établissent avec un but en tête et que l’objectif des individus est d’utiliser ces relations de manière bénéfique. Cette théorie est le moteur des hypothèses de recherche et des résultats de l’étude. L’hypothèse de l’étude est que l’implication dans les institutions religieuses a une corrélation positive sur un niveau plus élevé de capital social et que le capital social a une corrélation positive sur le bénévolat. Le capital social est donc vu comme une variable médiatrice entre un accroissement de l’implication religieuse et l’augmentation du bénévolat.